The EEG Ictal–Interictal Continuum—A Metabolic Roar But a Whimper of a Functional Outcome. Issue 4 (July 2019) - Lee, Jong Woo
Lateralized Periodic Discharges Frequency Correlates With Glucose Metabolism Subramaniam T, Jain A, Hall LT, Cole AJ, Westover MB, Rosenthal ES, Struck AF. Neurology. 2019;92(7):e670-e674. Objective: To investigate the correlation between characteristics of lateralized periodic discharges (LPDs) and glucose metabolism measured by (18)F-fluorodeoxyglucose (FDG)-positron emission tomography (PET). Methods: We retrospectively reviewed medical records to identify patients who underwent FDG-PET during electroencephalography (EEG) monitoring with LPDs present during the FDG uptake period. Two blinded board-certified neurophysiologists independently interpreted EEGs. (18)F-fluorodeoxyglucose uptake was measured using standardized uptake value (SUV). Structural images were fused with PET images to aid with localization of SUV. Two PET readers independently measured maximum SUV. Relative SUV values were obtained by normalization of the maximum SUV to the SUV of pons (SUVRpons). Lateralized periodic discharge frequency was analyzed both as a categorical variable and as a continuous measure. Other secondary variables included duration, amplitude, presence of structural lesion, and "plus" EEG features such as rhythmic or fast sharp activity. Results: Nine patients were identified and 7 had a structural etiology for LPDs. Analysis using frequency as a categorical variable and continuous variable showed an association between increased LPD frequency and increased ipsilateral SUVRpons ( P = .02). Metabolism associated with LPDs (0.5 Hz as a baseline) increased by a median of 100% at 1 Hz and for frequencies >1 Hz increased by a median of 309%. There were no statistically significant differences in SUVRpons for other factors including duration ( P = .10), amplitude ( P = .80), structural etiology ( P = .55), or "plus" features such as rhythmic or fast sharp activity ( P = .84). Conclusions: Metabolic activity increases monotonically with LPD frequency. Lateralized periodic discharge frequency should be a measure of interest when developing neuroprotection strategies in critical neurologic illness. : Continuous Electroencephalography After Moderate to Severe Traumatic Brain Injury Lee H, Mizrahi MA, Hartings JA, Sharma S, Pahren L, Ngwenya LB, Moseley BD, Privitera M, Tortella FC, Foreman B. Crit Care Med. 2019;47(4):574-582. Objectives: After traumatic brain injury, continuous electroencephalography is widely used to detect electrographic seizures. With the development of standardized continuous electroencephalography terminology, we aimed to describe the prevalence and burden of ictal–interictal patterns, including electrographic seizures after moderate to severe traumatic brain injury, and to correlate continuous electroencephalography features with functional outcome. Design: Post hoc analysis of the prospective, randomized controlled phase 2 multicenter INTREPID study (ClinicalTrials.gov : NCT00805818). Continuous electroencephalography was initiated upon admission to the intensive care unit. The primary outcome was the 3-month Glasgow Outcome Scale–Extended. Consensus electroencephalography reviews were performed by raters certified in standardized continuous electroencephalography terminology blinded to clinical data. Rhythmic, periodic, or ictal patterns were referred to as "ictal–interictal continuum"; severe ictal–interictal continuum was defined as greater than or equal to 1.5 Hz lateralized rhythmic delta activity or generalized periodic discharges and any lateralized periodic discharges or electrographic seizures. Setting: Twenty US level I trauma centers. PATIENTS: Patients with nonpenetrating traumatic brain injury and postresuscitation Glasgow Coma Scale score of 4 to 12 were included. Interventions: None. Measurements and main results: Among 152 patients with continuous electroencephalography (age = 34 ± 14 years; 88% male), 22 (14%) had severe ictal–interictal continuum including electrographic seizures in 4 (2.6%). Severe ictal–interictal continuum burden correlated with initial prognostic scores, including the International Mission for Prognosis and Analysis of Clinical Trials in Traumatic Brain Injury ( r = 0.51; P = .01) and Injury Severity Score ( r = 0.49; P = .01), but not with functional outcome. After controlling clinical covariates, unfavorable outcome was independently associated with absence of posterior dominant rhythm (common odds ratio, 3.38; 95% confidence interval, 1.30-9.09), absence of N2 sleep transients (3.69; 1.69-8.20), predominant delta activity (2.82; 1.32-6.10), and discontinuous background (5.33; 2.28-12.96) within the first 72 hours of monitoring. Conclusions: Severe ictal–interictal continuum patterns, including electrographic seizures, were associated with clinical markers of injury severity but not functional outcome in this prospective cohort of patients with moderate to severe traumatic brain injury. Importantly, continuous electroencephalography background features were independently associated with functional outcome and improved the area under the curve of existing, validated predictive models.